Socioeconomic Status of MS Patients in the Podkarpackie Voivodship — a Pilot Study - Sapuła, Rafał; Topolski, Adam; Sapuła, Joanna; Idzikowski, Michał; Rogowska, Sylwia (Regional Barometer. Analyses & Prognoses, 2014)
Multiple Sclerosis (MS) is a chronic disease of the nervous system. There are approximately 2 million people suffering from MS worldwide. Poland belongs to the countries with high MS incidence and presently the estimated number is 60 000. The neurologic deficiencies occurring in result of the disease have a negative impact on many aspects of life, including professional life. The aim of the study was to evaluate the socioeconomic status of the MS patients in the Podkarpackie Voivodship. The study covered 25 MS cases from the Podkarpackie Voivodship. In all cases, MS was diagnosed by a specialist. A survey consisting of 40 single-choice questions was designed for the purposes of the study. The analysis of the data obtained from the survey indicated that the majority of the MS patients are professionally inactive which has a negative impact on their economic status. The ability to work and perform ADLs decreases in patients aged 40 or more. The self-service functions and the abilities to perform housework also deteriorate with time. The patients require assistance and care from others.